Perkembangan teknologi digital dan pengaruhnya terhadap sistem pendidikan: upaya menigkatkan kualitas pembelajaran melalui pemanfaatan teknologi - Al hilal, Muhammad Nur Wahit (Maliki Interdisciplinary Journal, 2026)
The development of technology has brought fundamental changes to the educational ecosystem through massive educational transformation. This study aims to analyze how the integration of digital technology can support learning quality in the modern era. One of the primary strategies examined is the implementation of the blended learning model as a flexible and interactive learning solution. The research method used is descriptive lerning solution. The researce method used is descrptive qualitative with a literature study to evaluate the effectiveness of the collaboration between face-to-face and online learning. The analysis results indicate that the success of this innovation heavily depends on educator competence in managing digital tools and designing adaptive pedagogy. In conclusion, the synergy between technologycal infrastructure and human resource readiness is the key to realizing a high-quality educational system that is relevant to contemporary challenges.